Effects of cell phone dependence on the social skills of university students - De la Cruz Sandoval, Diana (2019)
Objective: To determine the relationship between cell phone dependency and social skills of thestudents of a private university in East Lima. Methodology: The non-experimental cross-sectionaland correlational type design was used. Likewise, an intentional non-probabilistic sampling was used,including students of both sexes with ages between 17 and 28 years. Results: 52.1% of universitystudents are at risk of presenting dependence to the cell phone, while 22.8% already have it, comparedto 25.1% who do not. Likewise, 56.1% of the students show a low level of social skills, 29.9% are inthe process of developing them and only 14% have developed social skills. In addition, a negative andsignificant relationship was found between the study variables (Rho= -, 645, p <0.01), in the sameway a negative and significant relationship was found in the cell dependency dimensions with the totalsocial skills: “abstinence “(Rho= -,624; p <0.01), “abuse and difficulty of controlling the impulse” (Rho=-, 526; p <0.01), “problems caused by excessive use” (Rho= -, 595; p <0.01) and “tolerance” (Rho=-, 569; p <0.01). Conclusion: Cell dependency is significantly related and inversely related to socialskills. That is, a higher level of cell phone dependency is associated with lower level of social skills isand vice versa.